The commercial functions of a trade mark, unconventional trade marks and modern technology (Fields)
The paper analyses the current legislation within the UK and Europe with respect to trade mark law. A number of legal journals and case reports provide the bulk of research material, with use of direct judicial quotes and key opinions of journal authors providing the framework for research into the state of current trade mark law. The historical functions of trade marks dating back nearly a century are still relevant today, with concepts recognised and enshrined by both domestic UK and European Union courts. Trade marks work as a badge of origin and, by extension, allow similar products to be differentiated. They act as a guarantee of quality and an ambassador for the generation and preservation of goodwill that has been generated within a given trade mark. Gaining a trade mark confers a near monopoly on its use and the legislation provides mechanisms to protect and recognise this. A trade mark allows businesses to build identity, quality and reputation into the core essence and branding of their products. A diverse quantity of ideas and concepts are capable of representation graphically, in both conventional and abstract forms, allowing them to be trade marked. The resulting monopoly granted by the trade mark is of exceptional importance to businesses of all sizes, allowing them to benefit from the breadth of commercial functions that a trade mark can fulfil. Despite the law regularly playing catch-up to new technological advances, the courts are applying flexible and practical solutions to accommodate the developing needs of modern informational technology.